Joy Hendry. 2018. Para entender la sociedad japonesa. Traducido por Francisco J. Ramos Mena. Barcelona: Bellaterra. 309 pp. - Quintairos-Soliño, Alba (El Colegio de México, 2020)
Hendry, Joy. 2018. Para entender la sociedad japonesa. Translated by Francisco J. Ramos Mena. Barcelona: Bellaterra. 309 pp.